2016
DOI: 10.1016/j.jvs.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evolving practice pattern changes and outcomes in the era of hybrid aortic arch repair

Abstract: Objective The role of hybrid repair in the management of aortic arch pathology, and long-term outcomes with these techniques, remains uncertain. We report a decade of experience with hybrid arch repair (HAR) and assess institutional practice patterns with regard to the use of hybrid and open techniques. Methods Hybrid and open total and distal arch procedures performed between July 2005 and January 2015 were identified from a prospectively maintained, institutional aortic surgery database. Perioperative morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…The literature search identified 1,268 records, of which nine satisfied the inclusion criteria and definitions for hybrid versus traditional aortic arch surgery (6,7,(18)(19)(20)(28)(29)(30)(31) (study details in Table S1). Two studies were identified as high quality, three as intermediate quality and four as standard quality using the adapted scoring criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search identified 1,268 records, of which nine satisfied the inclusion criteria and definitions for hybrid versus traditional aortic arch surgery (6,7,(18)(19)(20)(28)(29)(30)(31) (study details in Table S1). Two studies were identified as high quality, three as intermediate quality and four as standard quality using the adapted scoring criteria.…”
Section: Resultsmentioning
confidence: 99%
“…studies used as basis for exclusion (6,(18)(19)(20). Given the differing baseline patient characteristics of Sun's study, pooled Kaplan-Meier analysis excluding these results was conducted, showing better long-term survival and reduced death rate for conventional repair than hybrid repair ( Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endovascular arch procedures using branched or fenestrated endografts or open arch debranching have proven feasible, but remain technically challenging and anatomically treacherous due to a reliance on ascending aorta proximal landing zone (Ishimaru zone 0) 1 with the attendant risks of device migration, coronary or arch vessel occlusion, and retrograde dissection. 2 However, a more restrained application of proximal aorta endografting that avoids the technical challenges of arch vessel preservation entails isolated pavement of the supracoronary ascending aorta, from the sinotubular junction to the innominate artery, for select high-risk patients with focal aortic pathology contained wholly within this segment. However, this short arc of aorta is poorly accessible by standard percutaneous routes and no devices are specially designed for the unique length, diameter, and curvature specifications of the ascending aorta.…”
mentioning
confidence: 99%